Biological and Clinical Rationale for Androgen Priming in Ovarian Stimulation - Løssl, Kristine; Freiesleben, Nina la Cour; Wissing, Marie Louise; Birch Petersen, Kathrine; Holt, Marianne Dreyer; Mamsen, Linn Salto; Anderson, Richard A.; Andersen, Claus Yding (Frontiers in Endocrinology, 2020)
Androgen receptors are expressed by all stages of growing follicles, and follicular fluid androgen levels are positively correlated to granulosa cell androgen receptor and follicle-stimulating hormone (FSH) receptor expression. Thus, androgens may promote follicular growth, accumulation and/or responsiveness to gonadotropins. This is explored therapeutically in the concept of androgen priming, to improve the ovarian response to stimulation in assisted reproduction. Androgen effects may be achieved in two different ways, either directly by providing exogenous androgen or by providing luteinizing hormone (LH) activity (i.e. LH or human chorionic gonadotropin (hCG)) to stimulate local ovarian production of androgen. The androgen concentrations in follicular fluid by far exceed the levels in female circulation and it has recently been shown that there was no correlation between serum testosterone levels and follicular fluid androgen levels. There is some evidence that administration of exogenous dehydroepiandrosterone or testosterone increases live birth rates, but an optimal protocol has not been established and such adjuvant treatment should be considered experimental. Furthermore, studies exploring long-term administration of LH activity, achieving LH levels comparable to those seen in women with polycystic ovary syndrome, are awaited. The aim of the present review is to discuss critically the most suitable approach for androgen priming from a biological and clinical standpoint, and to evaluate current approaches and results obtained in clinical trials.